Magnetic Molecularly Imprinted Polymer Beads Obtained by Suspension Polymerization for the Adsorption of 2,4,6-Trichlorophenol from an Aqueous Solution in a Fixed-Bed Column - Ping Yu; Qilong Sun; Zhenjiang Tan; Minjia Meng; Jianming Pan; Yongsheng Yan; Chunxiang Li (Adsorption Science & Technology)
Highly effective magnetic molecularly imprinted polymer (MMIP) beads for adsorption of 2,4,6-trichlorophenol (2,4,6-TCP) were synthesized by suspension polymerization. The effect of various parameters such as bed depths (0.6, 1.1 and 1.7 cm), flow rate (1, 2 and 3 ml minute −1 ), influent 2,4,6-TCP concentrations (50, 100 and 200 mg l −1 ), influent solution pH (4, 6 and 8) and temperature (288, 298 and 308 K) was investigated. The breakthrough time increased with the increase of the bed depth, but decreased with an increase of the initial concentration, flow rate and temperature. The Adams–Bohart and Thomas models were applied to the adsorption process under experimental conditions to predict the breakthrough curves for process design. The Thomas model was in good agreement with the experimental data. Compared with magnetic non-imprinted polymers, MMIPs exhibited an excellent selectivity towards 2,4,6-TCP.